The Effect of Skill Level on the Timing of Childbearing and Number of Children - Peter Alders (Tinbergen Institute, 1998)
This paper examines the effect of differences in ability on the timing and number ofchildren. Higher skilled women have less disutility of labor and have relatively lessutility of raising children. Motherhood has a negative effect on the accumulation ofhuman capital by learning-by-doing and thereby on career perspectives. A decline infertility is explained without a quantity-quality shift.
Keywords: J13; J24; J22; 330; heterogeneity in skill level; number of children; timing childbearing; Bildung; Fertilität; Theorie